2021
DOI: 10.1016/j.ajic.2021.03.016
|View full text |Cite
|
Sign up to set email alerts
|

When planning meets reality: COVID-19 interpandemic survey of Michigan Nursing Homes

Abstract: Background Nursing home (NH) populations have borne the brunt of morbidity and mortality of COVID-19. We surveyed Michigan NHs to evaluate preparedness, staffing, testing, and adaptations to these challenges. Methods Inter-pandemic survey responses were collected May 1-12, 2020. We used Pearson's Chi-squared test, Fisher's exact test, and logistic regression to evaluate relationships. Results Of 452 Michigan NHs contacted via email, 145 (32.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(32 citation statements)
references
References 24 publications
2
30
0
Order By: Relevance
“…In line with other surveys of LTCH during the pandemic, we found that people working in LTCH felt ill-prepared and under-resourced, particularly where staffing was concerned [30][31][32]. Across front-line, administrative, and medical staff in our survey, there was consensus that there were not enough staff to support residents to remain safely in their rooms.…”
Section: Discussionsupporting
confidence: 85%
“…In line with other surveys of LTCH during the pandemic, we found that people working in LTCH felt ill-prepared and under-resourced, particularly where staffing was concerned [30][31][32]. Across front-line, administrative, and medical staff in our survey, there was consensus that there were not enough staff to support residents to remain safely in their rooms.…”
Section: Discussionsupporting
confidence: 85%
“…The COVID-19 pandemic adds to the danger experienced by these essential workers, with some studies forecasting increased burnout, turnover and staff shortages as a result. [619][620][621][622] According to "Making Care Work Pay," 610 shortages of direct care workers often leave care recipients and families scrambling to fill the gaps. As a result, many care recipients may find themselves unable to live as independently as they had hoped, moving to residential care settings sooner than they had planned and facing worsening health outcomes.…”
Section: Carementioning
confidence: 99%
“…According to the Paraprofessional Healthcare Institute's “Workplace Injuries and the Direct Care Workforce,” 618 in 2016 the number of injuries per 10,000 workers was 144 among personal care aides, 116 among home health aides and 337 among nursing assistants, compared with 100 per 10,000 workers across all occupations in the United States. The COVID‐19 pandemic adds to the danger experienced by these essential workers, with some studies forecasting increased burnout, turnover and staff shortages as a result 619–622 …”
Section: Workforcementioning
confidence: 99%
“…In other countries, reported barriers to facility‐wide serial testing during the first wave of the pandemic include insufficient availability of tests, limited personnel, insufficient financial resources, limited public health resources such as laboratory capacity, 17 , 18 , 19 , 20 and the discomfort of nasopharyngeal swabs. 21 In summer 2020, the availability of PCR tests and personal protective equipment (PEE) increased in the Netherlands, which eliminated some of these potential barriers.…”
Section: Introductionmentioning
confidence: 99%